2002
DOI: 10.1140/epja/i2002-10047-3
|View full text |Cite
|
Sign up to set email alerts
|

Explicit model realizing parton-hadron duality

Abstract: An explicit model realizing parton-hadron duality and fitting the data is suggested. Complex nonlinear Regge trajectories are important ingredients of the model. The inclusion of ∆ and N * trajectories should account for all resonances in the direct channel. The exotic trajectory is responsible for the smooth background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 19 publications
1
61
0
Order By: Relevance
“…The numbers presented in table 1 obtained with the code pptoll agrees with the Monte Carlo code lpair [9]. We note large differences between results obtained with the SU and the parametrizations by Fiore et al (labeled as FFJLM) [7] for inelastic-inelastic contribution for different models of F 2 structure functions, especially for high-p T cuts. We shall return to this point in the conclusion section.…”
Section: Results Of K T -Factorization Approachsupporting
confidence: 66%
See 1 more Smart Citation
“…The numbers presented in table 1 obtained with the code pptoll agrees with the Monte Carlo code lpair [9]. We note large differences between results obtained with the SU and the parametrizations by Fiore et al (labeled as FFJLM) [7] for inelastic-inelastic contribution for different models of F 2 structure functions, especially for high-p T cuts. We shall return to this point in the conclusion section.…”
Section: Results Of K T -Factorization Approachsupporting
confidence: 66%
“…The very low Q 2 region was parametrized in ref. [7] including pronounced resonance states by fitting data from SLAC and JLAB.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study [13] showed, that here it is best to use a parametrization of F 2 given in [14]. In the left panel of Fig.…”
Section: Pos(dis2016)205mentioning
confidence: 99%
“…[4] (see also earlier references cited there) and applied recently to the "golden plate" diffractive processes of J/Psi electroproduction The non-resonance direct-channel pole terms with exotic trajectories, dual to the Pomeron exchange, are (when applied to SDD, Q 2 should be replaced by −t and s by M 2 ) energy.…”
Section: And Sec 4 Of Ref [3])mentioning
confidence: 99%